ANALISIS SEJARAH PERKEMBANGAN BANK SYARIAH DAN IMPLIKASINYA TERHADAP KESEJAHTERAAN MASYARAKAT (STUDI KASUS DI BANK PEMBIAYAAN RAKYAT SYARIAH PATRIOT) - ANTO APRIYANTO; ARIE BUDIYANTO (Institut Bisnis Muhammadiyah Bekasi, 2020)
It’s aimed at addressing and knowing how closely the city’s relationship to Bekasi is as the struggle of Islam ists with the development of the finance society of shari, and it also relates the patriots Bank Pembiayaan Rakyat Syariah as the local shite financial institution that is capable of creating the Bank Pembiayaan Rakyat Syariah Patriot from since it was established and its implications irritated by the people of Bekasi, the study focused mode and more on the problems related to the Islam ics development history analysis of Bekasi and its implications for the public ‘s welfare (case study in Bank Pembiayaan Rakyat Syariah Patriot Bekasi) A mini research process uses qualitative research by extracting primary data sources through media interviews and direct surveys of data respondents or objective and secondary data, by reading books that can support discussions. And research for the city of Bekasi in the struggle of the muslims is the Islam ic warrior city it is not strange that the establishment of Bank Pembiayaan Rakyat Syariah is a reflection of the love of the financial institutions of Bekasi, so that the clove people can reduce the existing Bank Pembiayaan Rakyat Syariah of the patriot as the economy in the from of the growth in the economy in the from of the city and Bank Pembiayaan Rakyat Syaraih of the Patriot Bank Pembiayaan Rakyat Syariah has contributed to the growth of demurrity with various designed programs, weather by capitulation of mifid, and other such as mustofa the development of the economics growth of the Bekasi